SOCIALIZATION OF THE USE OF THE TOPLESPONIK SYSTEM FOR GROWING LETTUCE VEGETABLES IN LUTHU LAMWEU VILLAGE, SUKA MAKMUR DISTRICT, ACEH BESAR REGENCY: SOSIALISASI PENGGUNAAN SISTEM TOPLESPONIK UNTUK PERTUMBUHAN SAYUR SELADA DI DESA LUTHU LAMWEU KECAMATAN SUKA MAKMUR KABUPATEN ACEH BESAR - Mizar Liyanda; Sri Agustina; Mulyanti; Dewi Yana; Ade Zahara (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2024)
Luthu Lamweu Village is one of the villages located in Suka Makmur District, Aceh Besar Regency. This village has a very large agricultural land and lettuce plants are one of the main commodities. This community service activity aims to increase the knowledge and skills of the Luthu Lamweu Village Community regarding the manufacture and use of a toplesponik system for efficient, easy and fast growth of lettuce vegetables. Community Service activities consist of several lecturers assisted by several students conducting surveys and analyzing the situation in the village so that the problems that occur can be identified. The survey results show that one of the problems faced by the community is the low knowledge of the community about hydroponics. The solution to the problems faced by the community is through providing knowledge on how to make and use a good jarponik system on vegetable plants by utilizing the potential of natural resources in the village in improving community welfare. The people of Luthu Lamweu Village, especially the PKK mothers, were very enthusiastic in participating in this Community Service Activity. The result of this Community Service Activity is that the community has understood the process of making and using the topleponik system and can apply it so that it can meet their needs and improve the community's economic level.